Ammonia nitrogen detection method
By using the non-toxic indophenol blue method and multi-layered ammonia nitrogen test strips, the problem of using highly toxic substances and unstable reagents in existing ammonia nitrogen detection methods has been solved, realizing convenient, safe and environmentally friendly ammonia nitrogen detection, providing highly reliable quantitative data and a wide range of application scenarios.
Patent Information
- Application Number
- CN202511311459.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-15
- Publication Date
- 2025-12-05
AI Technical Summary
Existing ammonia nitrogen detection methods suffer from the use of highly toxic substances and unstable reagents, resulting in high operational risks, difficult handling, and the inability to achieve real-time monitoring.
Using the non-toxic indophenol blue method, the ammonia nitrogen test paper, composed of a porous membrane layer, a first reaction layer, a second reaction layer, and an absorbent pad bottom layer, combined with a standard colorimetric card, enables convenient, safe, and environmentally friendly ammonia nitrogen detection.
It achieves convenience, safety, and environmental friendliness in ammonia nitrogen detection, provides highly reliable quantitative data to support accurate decision-making, expands application scenarios, and has an extremely long shelf life at room temperature.
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of water quality detection, and particularly relates to an ammonia nitrogen detection method. BACKGROUND
[0002] The ammonia nitrogen detection method refers to a general term of various analysis technologies for determining the ammonia nitrogen content in water bodies. The ammonia nitrogen is not a single compound, but refers to the total of nitrogen in the form of free ammonia and ammonium ions. The ammonia nitrogen is a form of nitrogen in water bodies, mainly derived from the decomposition of nitrogen-containing organic matter, loss of chemical fertilizers and industrial wastewater. The ammonia nitrogen is a key core index in water quality evaluation, and has extremely important environmental and economic significance. The free ammonia has strong toxicity to aquatic organisms, and even a very low concentration can damage the gills of fish, leading to hypoxia and death. Meanwhile, the ammonia nitrogen is the first choice of nutrients for aquatic plants such as algae, and excessive ammonia nitrogen can lead to the crazy growth of algae, consume oxygen in water and destroy the ecological system. In addition, in the treatment of drinking water and wastewater treatment plants, the ammonia nitrogen concentration needs to be accurately controlled to ensure the treatment effect and the compliance of effluent.
[0003] The existing ammonia nitrogen detection methods mainly include the Nessler's reagent spectrophotometry and the indigo phenol blue method. However, the mercury iodide in the reagent used in the Nessler's reagent spectrophotometry is a highly toxic substance, which can cause serious harm to the central nervous system and kidneys of the operators. Meanwhile, a large amount of mercury-containing waste liquid generated in the process is extremely difficult and expensive to treat, and improper disposal can easily cause secondary pollution. The oxidizing agent sodium hypochlorite solution used in the indigo phenol blue method is very unstable, and is easily affected by light, temperature and pH value, and needs to be prepared on site or calibrated frequently, which is inconvenient to store and cannot provide results on site. The process from sampling to result output is long, and the real-time monitoring is lost.
[0004] In view of the above problems, the present application provides a solution. SUMMARY
[0005] The present application aims to provide an ammonia nitrogen detection method, which has the advantages of convenience, safety and environmental protection.
[0006] To achieve the above-mentioned purpose, the present application adopts the following technical scheme: an ammonia nitrogen detection method comprising the following steps:
[0007] S1: using a pipette to take 1ml of water sample with an ammonia nitrogen concentration to be detected, then filtering with sterile filter paper, and then adding into a test tube, adding 9ml of distilled water in the test tube, and shaking for 3-5s, then taking out two ammonia nitrogen detection test papers from a sealed aluminum foil bag, and immediately resealing the bag to prevent the remaining test papers from being damp and invalid;
[0008] S2: completely immersing the end of the ammonia nitrogen detection test paper into the water sample in the test tube to ensure sufficient wetting, gently touching the inner wall of the beaker to drain the excess water drops when taking out, and placing the test paper flat, and standing until the color of the end of the ammonia nitrogen detection test paper immersed in the water sample in the test tube is stable;
[0009] S3: immediately after the color development, the color of the end of the ammonia nitrogen test paper fully immersed in the test tube water sample is compared with the standard color card under natural light or bright light, the test paper is placed next to the standard color card, and the color block closest to the color of the reaction zone is found;
[0010] S4: read the ammonia nitrogen concentration value corresponding to the color block, then multiply the read ammonia nitrogen concentration value by 10 to obtain the ammonia nitrogen concentration value of the water sample to be tested, and after reading, the used test paper is treated as solid waste according to the laboratory waste.
[0011] Further, an ammonia nitrogen test paper is composed of four layers of a porous membrane layer, a first reaction layer, a second reaction layer and a water absorption pad bottom layer;
[0012] Further, the porous membrane layer is a polyethylene woven mesh with a thickness of 0.1 mm and a pore size of 10 um;
[0013] Further, the first reaction layer is composed of 0.4 mm polyester non-woven fabric and a first reaction liquid, wherein the first reaction liquid is composed of the following components: sodium salicylate, sodium hydroxide, sodium nitrosoferricyanide, potassium sodium tartrate and EDTA;
[0014] Further, the second reaction layer is composed of 0.3 mm cellulose filter paper and a second reaction liquid, wherein the second reaction liquid is composed of the following components: sodium dichloroisocyanurate, sodium carbonate and sodium bicarbonate;
[0015] Further, the water absorption pad bottom layer is a 0.9 g / cm 3 cellulose pad with a thickness of 1 mm;
[0016] Further, a preparation method of an ammonia nitrogen test paper comprises the following steps:
[0017] A1: take 1L deionized water and add it to the reaction kettle, first add 100g sodium hydroxide, set the stirrer speed to 300rpm, stir for 5min, cool naturally to room temperature after dissolution, then add 150g sodium salicylate, 30g potassium sodium tartrate and 5g EDTA, continue stirring at the same stirrer speed for 5min, then transfer to a light-proof environment, add 1g sodium nitrosoferricyanide, continue stirring at the same stirrer speed for 5min, then make up to 1L after stirring, obtain the first reaction liquid, store in the dark at 4℃;
[0018] A2: Take 1 L of deionized water into another reaction kettle, add 80 g of sodium dichloroisocyanurate, 15 g of sodium carbonate and 5 g of sodium bicarbonate in the dark environment, set the stirring speed to 1000 rpm, stir for 30 min, and then dilute to 1 L to obtain a second reaction solution, which is placed in a 4°C dark environment;
[0019] A3: Place the polyester non-woven fabric in the first impregnation tank, the impregnation liquid is the first reaction liquid, use the metering roller to control the polyester non-woven fabric to adsorb the first reaction liquid with a weight of three times that of the polyester non-woven fabric, obtain the first carrier, and place the cellulose filter paper in the second impregnation tank, the impregnation liquid is the second reaction liquid, use the metering roller to control the cellulose filter paper to adsorb the second reaction liquid with a weight of 1.5 times that of the cellulose filter paper, obtain the second carrier;
[0020] A4: Place the first carrier and the second carrier in a 50°C low-temperature drying box respectively, and dry for 20 min, then obtain the first reaction layer and the second reaction layer;
[0021] A5: Place the porous membrane layer, the first reaction layer, the second reaction layer and the water absorption pad bottom layer in order from top to bottom, lay a layer of 0.5 um food pressure sensitive adhesive between each layer, then transfer to a laminator with an environmental humidity of less than 20%, set the laminator temperature to 25°C and the pressure to 0.5 MPa, and obtain the composite board after lamination;
[0022] A6: Use a precision rotary cutting machine to cut the composite board into a long strip-shaped test paper with a length of 60 mm and a width of 5 mm, quickly put the cut test paper into an aluminum foil bag, vacuumize the aluminum foil bag containing the test paper, and then heat seal to obtain an ammonia nitrogen detection test paper.
[0023] Further, a preparation method of a standard colorimetric card comprises the following steps:
[0024] B1: Prepare an ammonium chloride standard solution with a concentration gradient of ammonia nitrogen, with concentrations of 2 mg / L, 5 mg / L, 8 mg / L, 10 mg / L, 15 mg / L, 20 mg / L and 50 mg / L;
[0025] B2: Dip the end of the ammonia nitrogen detection test paper into the standard solution with a concentration gradient, ensuring that it is fully wetted, and gently touch the inside wall of the beaker to remove excess water droplets when taking it out, then place the test paper flat and let it stand until the end of the test paper immersed in the test tube water sample is color stable;
[0026] B3: After color development, prepare a standard color block according to the color development result, then arrange the standard color blocks in order according to the concentration of the ammonia nitrogen standard solution, and obtain a standard colorimetric card.
[0027] In conclusion, by adopting the technical scheme, the application has the advantages that the non-toxic indigo phenol blue method is adopted to completely avoid the harm of the mercury test paper to the environment and the operator, and the waste treatment is simple; meanwhile, by accurately controlling the carrier liquid rate and the reagent ratio and the uniform microfluidic structure, the consistency of the reaction of each test paper is ensured, the built-in potassium sodium tartrate and EDTA can effectively complex the metal ions in the water sample to prevent the generation of precipitate and the occurrence of side reactions, highly reliable quantitative data are provided for the user to support the accurate decision based on the data, the complex water bodies such as the underground water, the seawater and the industrial wastewater can be directly detected, the application scenarios are widened, the incompatible reagents are physically isolated, the spontaneous decomposition reaction during the storage is fundamentally eliminated, and the shelf life at room temperature is extremely long. DETAILED DESCRIPTION
[0028] In order to make the technical means, creative features, purposes and effects of the application easy to understand, the application is further described below in combination with specific embodiments.
[0029] In the following examples, the experimental methods are all conventional methods, and are carried out according to the techniques or conditions described in the literature in the field or according to the product instructions, unless otherwise specified. The materials and reagents used in the following examples can be obtained from commercial channels, unless otherwise specified.
[0030] Example 1
[0031] 1: Take 1L deionized water and add it to a reaction kettle, first add 100g sodium hydroxide, set the stirrer speed to 300rpm, stir for 5min, after dissolution, naturally cool to room temperature, then add 150g sodium salicylate, 30g potassium sodium tartrate and 5g EDTA, continue stirring at the same stirrer speed for 5min, then transfer to a light-proof environment, add 1g sodium nitroprusside, continue stirring at the same stirrer speed for 5min, after stirring, make up to 1L to obtain a first reaction liquid, store in a light-proof environment at 4℃;
[0032] 2: Take 1L deionized water and add it to another reaction kettle, add 80g sodium dichloroisocyanurate, 15g sodium carbonate and 5g sodium bicarbonate in a light-proof environment, set the stirrer speed to 1000rpm, stir and dissolve for 30min, after dissolution, make up to 1L to obtain a second reaction liquid, store in a light-proof environment at 4℃;
[0033] 3: Place 300g polyester non-woven fabric in the first impregnation tank, the impregnation liquid is the first reaction liquid, use a metering roller to control the polyester non-woven fabric to adsorb the first reaction liquid with a weight of 900g, to obtain a first carrier, place 300g cellulose filter paper in the second impregnation tank, the impregnation liquid is the second reaction liquid, use a metering roller to control the cellulose filter paper to adsorb the second reaction liquid with a weight of 450g, to obtain a second carrier;
[0034] 4: The first carrier and the second carrier are placed in a 50°C low-temperature drying oven, respectively, and dried for 20 min. After drying, the first reaction layer and the second reaction layer are obtained;
[0035] 5: The porous membrane layer, the first reaction layer, the second reaction layer and the water absorption pad bottom layer are placed in the order from top to bottom, and a layer of 0.5 um food pressure-sensitive adhesive is laid between each layer. Then, it is transferred to a laminator with an environmental humidity of less than 20%, and the laminator temperature is set to 25°C and the pressure is set to 0.5 MPa. After lamination, the composite board is obtained;
[0036] 6: The composite board is cut into a long strip-shaped test paper with a length of 60 mm and a width of 5 mm using a precision rotary cutting machine. The cut test paper is quickly loaded into an aluminum foil bag, the aluminum foil bag containing the test paper is vacuumed, and then heat-sealed to obtain the ammonia nitrogen test paper prepared in Example 1.
[0037] 7: Prepare ammonium chloride standard solutions with different concentrations of ammonia nitrogen, with concentrations of 2 mg / L, 5 mg / L, 8 mg / L, 10 mg / L, 15 mg / L, 20 mg / L and 50 mg / L, respectively;
[0038] 8: The end of the ammonia nitrogen test paper is completely immersed in the standard solution with a concentration gradient, ensuring sufficient wetting. When taking out, gently touch the inside wall of the beaker to drain the excess water droplets. Place the test paper flat and let it stand until the end of the test paper immersed in the test tube water sample is color stable;
[0039] 9: After color stabilization, prepare standard color blocks according to the color results. Then arrange the standard color blocks in order according to the concentration of the ammonia nitrogen standard solution to obtain the standard colorimetric card prepared in Example 1.
[0040] Example 2
[0041] 1: Take 1L of deionized water and add it to the reaction kettle. First, add 100g of sodium hydroxide, set the stirrer speed to 300rpm, and stir for 5min. After dissolution, naturally cool to room temperature. Then add 150g of sodium salicylate, 30g of potassium sodium tartrate and 5g of EDTA. Continue stirring at the same speed for 5min. Then transfer to a light-proof environment and add 1g of sodium nitroprusside. Continue stirring at the same speed for 5min. After stirring, make up to 1L to obtain the first reaction solution. Store in the dark at 4°C;
[0042] 2: Take 1L of deionized water and add it to another reaction kettle. In a light-proof environment, add 80g of sodium dichloroisocyanurate, 15g of sodium carbonate and 5g of sodium bicarbonate. Set the stirrer speed to 1000rpm and stir for 30min. After dissolution, make up to 1L to obtain the second reaction solution. Store in a light-proof environment at 4°C;
[0043] 3: Place 500 g of polyester non-woven fabric in the first impregnation tank, and the impregnation liquid is the first reaction liquid. Use a metering roller to control the absorption of the first reaction liquid by the polyester non-woven fabric to a weight of 1 kg, and obtain the first carrier. Place 500 g of cellulose filter paper in the second impregnation tank, and the impregnation liquid is the second reaction liquid. Use a metering roller to control the absorption of the second reaction liquid by the cellulose filter paper to a weight of 500 g, and obtain the second carrier;
[0044] 4: Place the first carrier and the second carrier in a 50°C low-temperature drying box, respectively, and dry for 20 min. After drying, obtain the first reaction layer and the second reaction layer;
[0045] 5: Place the porous membrane layer, the first reaction layer, the second reaction layer, and the water absorption pad bottom layer in order from top to bottom, and lay a layer of 0.5 um food pressure-sensitive adhesive between each layer. Then, transfer to a laminator with an environmental humidity of less than 20%, and set the laminator temperature to 25°C and the pressure to 0.5 MPa. After lamination, obtain the composite board;
[0046] 6: Use a precision rotary cutting machine to cut the composite board into a long strip-shaped test paper with a length of 60 mm and a width of 5 mm. Quickly load the cut test paper into an aluminum foil bag, vacuumize the aluminum foil bag containing the test paper, and then heat seal to obtain the ammonia nitrogen test paper prepared in Example 2.
[0047] 7: Prepare ammonium chloride standard solutions with different concentrations of ammonia nitrogen, with concentrations of 2 mg / L, 5 mg / L, 8 mg / L, 10 mg / L, 15 mg / L, 20 mg / L, and 50 mg / L, respectively;
[0048] 8: Completely immerse the end of the ammonia nitrogen test paper in the standard solution with a concentration gradient, ensuring sufficient wetting. When taking out, gently touch the inside wall of the beaker to drain the excess water droplets. Place the test paper flat and let it stand until the end of the test paper immersed in the test tube water sample is color stable;
[0049] 9: After color stabilization, prepare standard color blocks according to the color results. Then, arrange the standard color blocks in order according to the concentrations of the ammonia nitrogen standard solution, and obtain the standard colorimetric card prepared in Example 2.
[0050] Example 3
[0051] The water sample in this example is from municipal sewage;
[0052] 1: Use a pipette to take 1 ml of municipal sewage, then filter it with sterile filter paper, and then add it to a test tube. Add 9 ml of distilled water to the test tube and shake for 5 s to obtain a municipal sewage water sample. After shaking, take out two ammonia nitrogen test papers from the sealed aluminum foil bag and immediately reseal the bag to prevent the remaining test paper from being damp and ineffective;
[0053] 2: The end of the ammonia nitrogen test paper is completely immersed in the municipal sewage water sample, ensuring sufficient wetting. When taking out, gently touch the inner wall of the beaker to drain the excess water droplets. Place the test paper flat and let it stand until the end of the ammonia nitrogen test paper immersed in the municipal sewage water sample develops color stably.
[0054] 3: Immediately after color development stability, compare the color of the end of the ammonia nitrogen test paper completely immersed in the municipal sewage water sample with the standard color card under natural light or bright light. Place the test paper next to the standard color card and find the color block closest to the reaction zone color.
[0055] 4: Read the ammonia nitrogen concentration value corresponding to the color block. Then multiply the read ammonia nitrogen concentration value by 10 to get the ammonia nitrogen concentration value of the municipal sewage detected in Example 3, which is 22.3 mg / L. After reading, the used test paper is treated as solid waste according to laboratory waste.
[0056] Example 4
[0057] The water sample in this example is from food processing wastewater.
[0058] 1: Use a pipette to take 1 ml of food processing wastewater, then filter with sterile filter paper. Add 9 ml of distilled water to the test tube and shake for 3 seconds to obtain the food processing wastewater sample. After shaking, take out two ammonia nitrogen test papers from the sealed aluminum foil bag and immediately reseal the bag to prevent the remaining test paper from being damp and ineffective.
[0059] 2: The end of the ammonia nitrogen test paper is completely immersed in the food processing wastewater water sample, ensuring sufficient wetting. When taking out, gently touch the inner wall of the beaker to drain the excess water droplets. Place the test paper flat and let it stand until the end of the ammonia nitrogen test paper immersed in the food processing wastewater water sample develops color stably.
[0060] 3: Immediately after color development stability, compare the color of the end of the ammonia nitrogen test paper completely immersed in the municipal sewage water sample with the standard color card under natural light or bright light. Place the test paper next to the standard color card and find the color block closest to the reaction zone color.
[0061] 4: Read the ammonia nitrogen concentration value corresponding to the color block. Then multiply the read ammonia nitrogen concentration value by 10 to get the ammonia nitrogen concentration value of the food processing wastewater water sample, which is 43.6 mg / L. After reading, the used test paper is treated as solid waste according to laboratory waste.
[0062] Comparative Example 1
[0063] The first example of the Chinese patent with publication number CN104568936A is selected as Comparative Example 1.
[0064] Comparative Example 2
[0065] Example 1 of Chinese patent with publication number CN117007583A was selected as Comparative Example 2.
[0066] Detection performance test
[0067] 1: Prepare ammonium chloride standard solution with gradient of ammonia nitrogen concentration, the concentrations are 0.5 mg / L, 2 mg / L, 5 mg / L, 8 mg / L, 10 mg / L, 15 mg / L, 20 mg / L, and 50 mg / L, respectively;
[0068] 2: Use the ammonia nitrogen test paper prepared by Example 1, Example 2, Comparative Example 1 and Comparative Example 2 respectively to determine the ammonia nitrogen concentration, then compare with the theoretical value of the standard solution, and calculate the recovery rate;
[0069] 3: Select 0.5 mg / L, 10 mg / L and 50 mg / L standard solution, use the ammonia nitrogen test paper prepared by Example 1, Example 2, Comparative Example 1 and Comparative Example 2 respectively to determine the ammonia nitrogen concentration of the standard solution, each sample is determined for 20 times continuously, get the average value and standard deviation of each group of results, and calculate the relative standard deviation (RSD);
[0070] 4: Add 1 mg / L of Mg 2+ , Cu 2+ and humic acid to the 2 mg / L standard solution respectively, then use the ammonia nitrogen test paper prepared by Example 1, Example 2, Comparative Example 1 and Comparative Example 2 respectively to determine the ammonia nitrogen concentration of the standard solution, then compare with the theoretical value of the standard solution, and calculate the recovery rate;
[0071] 5: Use the ammonia nitrogen test paper prepared by Example 1, Example 2, Comparative Example 1 and Comparative Example 2 respectively to determine the ammonia nitrogen concentration of the 2 mg / L standard solution, and accurately record the time required for the test paper from immersion in the solution to complete color development with a stopwatch, and get the color development time.
[0072] Table 1, detection performance test results
[0073] Item Example 1 Example 2 Comparative Example 1 Comparative Example 2 Recovery 98% 99% 88% 94% Precision (RSD) 3% 2% 14% 11% Mg 2+ recovery after interference 97.8% 98.7% 81.6% 92.2% Cu 2+ recovery after interference 97.9% 98.8% 82.1% 92.5% Recovery after humic acid interference 97.8% 98.8% 86.3% 92.2% Color development time 3 min 3 min 8 min 6 min
[0074] From the analysis of Table 1, it can be seen that the ammonia nitrogen test paper prepared by Example 1 and Example 2 is closer to the true value, with smaller deviation, more reliable quantification, excellent repeatability, and good consistency of results of different test papers and different batches. The ammonia nitrogen test paper prepared by Comparative Example 1 and Comparative Example 2 is easily interfered by Cu 2+ , Mg 2+ and humic acid. The ammonia nitrogen test paper prepared by Example 1 and Example 2 can effectively eliminate the interference of hardness and various metal ions, and has shorter color development time.
[0075] Stability test
[0076] The ammonia nitrogen test paper prepared by example 1, example 2, comparative example 1 and comparative example 2 was placed in a constant temperature oven at 37℃, and was taken out periodically at 1, 2, 4 weeks, and then performance test was carried out, and the performance test method was the same as the detection performance test;
[0077] Table 2, stability test results
[0078] Performance test results after constant temperature for 1 week Example 1 Example 2 Comparative Example 1 Comparative Example 2 Recovery 96.04% 97.02% 77.44% 82.72% Precision (RSD) 4.94% 3.94% 24.32% 21.68% Mg 2+ recovery after interference 95.84% 96.73% 71.81% 81.14% Cu 2+ recovery after interference 95.94% 96.82% 72.24% 81.4% Recovery after humic acid interference 95.84% 96.82% 76.21% 81.14% Color development time 3 min 3 min 8 min 6 min Performance test results after constant temperature for 2 weeks Example 1 Example 2 Comparative Example 1 Comparative Example 2 Recovery 94.08% 95.04% 68.64% 73.32% Precision (RSD) 6.88% 5.92% 32.92% 30.58% Mg 2+ recovery after interference 93.89% 94.75% 62.65% 71.92% Cu 2+ recovery after interference 93.98% 94.85% 64.04% 72.15% Recovery after humic acid interference 93.89% 94.85% 67.31% 71.92% Color development time 3 min 3 min 8 min 6 min Performance test results after constant temperature for 4 weeks Example 1 Example 2 Comparative Example 1 Comparative Example 2 Recovery 91.14% 92.07% 57.2% 61.1% Precision (RSD) 9.79% 8.86% 44.1% 42.15% Mg 2+ recovery after interference 90.95% 91.79% 53.04% 59.93% Cu 2+ recovery after interference 91.05% 91.88% 53.37% 60.13% Recovery after humic acid interference 90.95% 91.88% 56.1% 59.93% Color development time 3 min 3 min 8 min 6 min
[0079] From the analysis of table 2, it can be seen that the ammonia nitrogen test paper prepared by example 1 and example 2 has good stability, and the ammonia nitrogen test paper prepared by comparative example 1 and comparative example 2 has begun to significantly decompose each other when constant temperature aging for one week, and the ammonia nitrogen test paper prepared by example 1 and example 2 only has a small amount of deliquescence, and the attenuation is weak; after constant temperature aging for two weeks, the ammonia nitrogen test paper prepared by comparative example 1 and comparative example 2 fails to accelerate, and the ammonia nitrogen test paper prepared by example 1 and example 2 still maintains the intended stability; after constant temperature aging for four weeks, the ammonia nitrogen test paper prepared by comparative example 1 and comparative example 2 has approached failure, and the results are completely unreliable, while the performance of the ammonia nitrogen test paper prepared by example 1 and example 2 still maintains more than 90%, and shows extremely long theoretical shelf life.
[0080] The above shows and describes the basic principles and main features of the present application and the advantages of the present application. It should be understood by those skilled in the art that the present application is not limited by the above examples, and the above examples and descriptions in the specification are only to illustrate the principles of the present application, and various changes and improvements can be made to the present application without departing from the spirit and scope of the present application, and these changes and improvements all fall within the scope of the present application. The scope of protection of the present application is defined by the appended claims and their equivalents.
Claims
1. A method for detecting ammonia nitrogen, characterized by, It comprises the following steps: S1: using a pipette to measure 1ml of water sample with ammonia nitrogen concentration to be tested, then using sterile filter paper to filter and add into a test tube, adding 9ml of distilled water into the test tube and shaking for 3-5s, after shaking, taking out two ammonia nitrogen test papers from a sealed aluminum foil bag and immediately resealing the bag to prevent the remaining test papers from being damp and invalid; S2: completely immersing the end of the ammonia nitrogen test paper into the water sample in the test tube to ensure sufficient wetting, gently touching the inner wall of the beaker to drain the excess water drops, and placing the test paper flat and standing until the end of the ammonia nitrogen test paper immersed in the water sample in the test tube is color stable; S3: after color stability, immediately comparing the color of the end of the ammonia nitrogen test paper immersed in the water sample in the test tube with the standard color card under natural light or bright light, placing the test paper beside the standard color card, and finding the color block closest to the color of the reaction area; S4: reading the ammonia nitrogen concentration value corresponding to the color block, then multiplying the read ammonia nitrogen concentration value by 10 to obtain the ammonia nitrogen concentration value of the water sample to be tested, and after reading, disposing the used test paper as solid waste according to the laboratory waste treatment.
2. An ammonia nitrogen test paper, characterized by, The porous membrane layer, the first reaction layer, the second reaction layer and the water absorption pad bottom layer are four layers.
3. The test paper for ammonia nitrogen according to claim 2, wherein The porous membrane layer is a polyethylene woven mesh with a thickness of 0.1mm and a pore size of 10um.
4. The test paper for ammonia nitrogen according to claim 2, wherein The first reaction layer is composed of 0.4mm polyester non-woven fabric and a first reaction solution, wherein the first reaction solution is composed of the following components: sodium salicylate, sodium hydroxide, sodium nitroprusside, potassium sodium tartrate and EDTA.
5. The test paper for ammonia nitrogen according to claim 2, wherein The second reaction layer is composed of 0.3mm cellulose filter paper and a second reaction solution, wherein the second reaction solution is composed of the following components: sodium dichloroisocyanurate, sodium carbonate and sodium bicarbonate.
6. The test paper for ammonia nitrogen according to claim 2, wherein The water-absorbing pad base is a 0.9 g / cm 3 cellulose pad with a thickness of 1 mm.
7. The method for preparing an ammonia nitrogen test paper according to claim 2, characterized in that, It comprises the following steps: A1: taking 1L of deionized water and adding it into a reaction kettle, first adding 100g of sodium hydroxide, setting the stirrer speed to 300rpm, stirring for 5min, naturally cooling to room temperature after dissolution, then adding 150g of sodium salicylate, 30g of potassium sodium tartrate and 5g of EDTA, keeping the stirrer speed unchanged and continuously stirring for 5min, then transferring to a light-proof environment, adding 1g of sodium nitroprusside, keeping the stirrer speed unchanged and continuously stirring for 5min, after stirring, making up to 1L to obtain the first reaction solution, storing in a light-proof environment at 4℃; A2: taking 1L of deionized water and adding it into another reaction kettle, adding 80g of sodium dichloroisocyanurate, 15g of sodium carbonate and 5g of sodium bicarbonate in a light-proof environment, setting the stirrer speed to 1000rpm, stirring and dissolving for 30min, after dissolution, making up to 1L to obtain the second reaction solution, and placing in a light-proof environment at 4℃; A3: placing the polyester non-woven fabric in the first immersion tank, the immersion liquid is the first reaction solution, using a metering roller to control the weight of the polyester non-woven fabric adsorbing the first reaction solution to be 2-3 times the weight of the polyester non-woven fabric, obtaining the first carrier, placing the cellulose filter paper in the second immersion tank, the immersion liquid is the second reaction solution, using a metering roller to control the weight of the cellulose filter paper adsorbing the second reaction solution to be 1-1.5 times the weight of the cellulose filter paper, obtaining the second carrier; A4: The first carrier and the second carrier are respectively placed in a 50°C low-temperature drying box and dried for 20 min, and the first reaction layer and the second reaction layer are obtained after drying; A5: The porous membrane layer, the first reaction layer, the second reaction layer and the water absorption pad bottom layer are arranged in the order from top to bottom, a layer of 0.5um food pressure sensitive adhesive is laid between each layer, and then transferred to a laminator with an environmental humidity less than 20%, the laminator temperature is set to 25°C and the pressure is set to 0.5MPa, and the composite board is obtained after lamination; A6: The composite board is cut into a long strip-shaped test paper with a length of 60mm and a width of 5mm using a precision rotary cutting machine, the cut test paper is quickly loaded into an aluminum foil bag, the aluminum foil bag containing the test paper is vacuumized, and then heat sealed to obtain an ammonia nitrogen detection test paper.
8. A method of producing a standard color chart, characterized by, The steps include: B1: Prepare ammonium chloride standard solution with ammonia nitrogen concentration gradient, the concentrations are 2mg / L, 5mg / L, 8mg / L, 10mg / L, 15mg / L, 20mg / L and 50mg / L respectively; B2: The end of the ammonia nitrogen detection test paper is completely immersed in the standard solution with concentration gradient, and the test paper is placed flat and left to stand until the end of the test paper immersed in the test tube water sample is color stable; B3: After color stabilization, prepare standard color blocks according to the color results, and then arrange the standard color blocks in the order of ammonia nitrogen standard liquid concentration to obtain a standard color card.
Citation Information
Patent Citations
Ammonia nitrogen test paper and application method thereof
CN104568936A
Ammonia nitrogen detection reagent applicable to water automatic ammonia nitrogen detection system
CN107764759A
Water quality ammonia nitrogen rapid detection test paper and preparation method and detection method thereof
CN112834495A
Kit / test paper for detecting ammonia nitrogen, detection system and related method thereof
CN117007583A
Accurate determination method applied to ammonia nitrogen in complex water body
CN119164941A